Two new Spariolenus Simon, 1880 species from Pamir Mountains in Tajikistan – the first representatives of Heteropodinae in Central Asia - Fomichev, Alexander A. (Acta Biologica Sibirica, 2024)
Two new species of Spariolenus Simon, 1880, S. badakhshanicus sp. n. (♂♀) and S. darvazicus sp. n. (♀), are described from Pamir Mountains in eastern Tajikistan. They represent the first records of Heteropodinae in Central Asia. The type localities of new species in West Pamir are remote approximately 500 km north from the closest known locality of the subfamily, represented by S. lindbergi (Roewer, 1962), in Afghanistan. Both new species were collected at night in rocky habitats. Detailed descriptions, digital photographs of the new species, and a distributional map of all known Spariolenus species are provided.